Phytochemical Evaluation of Bark of Chirbilva Holoptelea integrifolia Planch. (International Journal of Ayurveda and Pharma Research, 2023)
Purpose: This study serve the purpose of standardization of bark of Chirbilva Holoptelea integrifolia an Ayurvedic drugs mentioned in classics. Methods: Drug is studied both qualitatively and quantitatively. Bark was air-dried under net in sun and fine powdered. Fine powdered was taken for phytochemical analysis. Results: Phytochemical study reveals phytochemical standardization of plant material With preliminary phytochemical analysis of drugs, presence or absence of primary and secondary metabolites was exposed. Carbohydrates, protein, alkaloids and cardiac glycosides were slightly present in bark. Flavonoid was moderately present and contains important compounds such as gallic acid, quercetin catechin, rutin, hyperoside and chlorogenic acid. Conclusion: Finding of this study laid a specific background for further research on extracts of stem bark of Holoptelea integrifolia for identification, purification, isolation of compounds having anti-inflammatory, digestive, carminative, laxative, anthelmintic, depurative revulsive, hypolipidemic and urinary astringent properties.